Product cost calculations of various designs of conventional solar still systems - Shukla S.K. (My University, 2025)
On the basis of experimental results obtained during performance evaluation of five types of solar stills, kept in outdoor conditions on a single plate form, the cost of distilled water produced have been calculated by using a uniform cost analysis method. The experiments were performed at IIT Delhi, India during the years 2001–2002 under summer and winter, both the climatic conditions. It can be concluded that the cost of distilled water produced from a multiwick double slope solar (DSMS) still is lesser than other solar stills due to higher yield/hour. However, for small scale purposes, multiwick single slope solar (SMS) still is a better option. Copyright © 2009 Inderscience Enterprises Ltd.